Effects of RFamide-related peptide-1 (RFRP-1) microinjections into the central nucleus of amygdala on passive avoidance learning in rats. (April 2017) - Kovács, Anita; László, Kristóf; Zagoracz, Olga; Ollmann, Tamás; Péczely, László; Gálosi, Rita; Lénárd, László
Abstract: The amygdaloid body (AMY) plays an important role in memory, learning and reward-related processes. RFRP-1 immunoreactive fibers and NPFF receptors were identified in the AMY, and previously we verified that RFRP-1 infused into the central nucleus of AMY (CeA) induced place preference. The aim of the present study was to examine the possible effects of RFRP-1 in the CeA on passive avoidance learning. Male Wistar rats were examined in two-compartment passive avoidance paradigm. Animals were shocked with 0.5 mA current and subsequently were microinjected bilaterally with 50 ng or 100 ng RFRP-1 in volume of 0.4 μl, or 20 ng NPFF receptor antagonist RF9 (ANT) alone, or antagonist 15 min before 50 ng RFRP-1 treatments into the CeA. Fifty nanogram dose of RFRP-1 significantly increased the step-through latency time, the 100 ng RFRP-1 and the ANT alone were ineffective. The effect of 50 ng RFRP-1 was eliminated by the ANT pretreatment. Our results suggest that intraamygdaloid RFRP-1 enhances learning processes and memory in aversive situations and this effect can specifically be prevented by ANT pretreatment. Highlights: RFRP-1 belonging to the RFamide peptide family was microinjected to the amygdala. The lower dose of RFRP-1 facilitates passive avoidance learning while higher dose is ineffective. NPFF receptor antagonist RF9 pretreatment prevents learning enhancing effects of RFRP-1 in the central nucleus of amygdala. These results are the first to show intraamygdaloid RFRP-1 enhances learning and memory processes in aversive situations.